Interaction of β2-Glycoprotein-I with Human Blood Platelets: Influence Upon the ADP-Induced Aggregation - Nimpf, Johannes; Wurm, Helmut; Kostner, Gerhard M (Thrombosis and Haemostasis, 1985)
The interaction of β2-glycoprotein-I (β2-G-I), a plasma constituent of unknown function, with blood platelets was studied. The following results were obtained: 1) β2-G-I binds to washed human platelets isolated by centrifugation (WP) at one kind of specific, saturable binding sites. The dissociation constant was found to be approx. 1 × 10−6M.2) In the presence of physiological concentrations of Ca++ (2.5 mM), this specific binding is markedly reduced. Unspecific binding of β2-G-I to platelets, however, is not influenced by Ca++.3) Platelets prepared by gel filtration (GFP), differing in their in vitro aggregability from WP, exhibit no specific binding of β2-G-I. Binding to GFP is also not induced by activation with thrombin, collagen or ADP.4) β2-G-I causes significant alteration of the ADP-induced aggregation of GFP. Aggregation induced by thrombin, collagen, arachidonic acid or PAF-acether, however is not altered by β2G-I.It is suggested, that pelleting during centrifugation causes irreversible rearrangements in the membrane of platelets.
Keywords: β2-glycoprotein-I; Platelets; ADP-aggregation